The northern region of Korea : history, identity & culture - Kim, Sun Joo, 1962- (Center For Korea Studies Publications., 2010)
For many centuries the residents of the three northern provinces of Korea have long had cultural and linguistic characteristics that have marked them as distinct from their brethren in the central area near the capital and in the southern provinces. Contributors to this book address the problem of amnesia regarding the subjectivity of the northern region of Korea in contemporary, historical, and cultural discourses, which have largely been dominated by grand paradigms, such as modernization theory, the positivist perspective, and Marxism. Through the use of storytelling, linguistic analysis, and journal entries from turn-of-the-century missionaries and traveling Russians in addition to many varieties of unconventional primary sources, they creatively explore unfamiliar terrain while examining the culture, identity, and regional distinctiveness of the northern region and its people.